Lactobacillus: A Probiotic Modulator of Gastrointestinal Motility - Wu, Richard You. (The Meducator, 2012)
Richard is a third year student in the Bachelor of Health Sciences (Honours) Program and a recipient of the Bachelor of Health Sciences Summer Research Scholarship. He spent his past summer researching the physiological e!ects that Lactobacillus reuteri evoke on murine gastrointestinal motility. The central focus of his research is to characterize these e!ects to better understand the communication between bene"cial gut microorganisms and the host nervous system.